Peraturan Hukum Pidana Bagi Perempuan Pelaku Aborsi Dari Korban Perkosaan - Elisa, Nufaris (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In this study, issues regarding legal protection and legal consequences for female abortion victims of rape from the threat of criminal prosecution of abortion are formulated. Abortive acts are prohibited by statute, and perpetrators are subject to criminal sanctions. However, abortions can be performed with exceptions, i.e. performed because of medical indications and rape victims. Abortion performed by the female of a rape victim, should be entitled to legal protection in view of the suffering she experiences both physically and psychically. The study uses a normative jurisprudential approach method, with the specification of analytical descriptive research. The data used in this study were primary data and secondary data, obtained through interviews and library studies, which were then analyzed qualitatively. Basically there are no legal consequences for the woman perpetrator of abortion of the victim of rape, because the act of performing an abortion due to the presence of force based on Article 48 of the Penal Code and the rule of permission of abortion based on Article 75 paragraph (2) of Law No. 306 te9ta9. without medical indication and criminal prosecution of rape, then for the perpetrator is subjected to criminal sanctions based on: (a) Article 194 of Law Number 36 of 2009, (b) Article 299 of the Penal Code, (c) Article 346 of the Penal Code, (d) Article, 34f) of the Penal Code 349 Criminal Code. Whereas for offenders of the criminal act of rape punishable under: (a) Section 285 of the Penal Code, (b) Section 286 of the Penal Code, (c) Section 287 of the Penal Code, and (e) Section 289 of the Penal Code.